Historic changes in the fire-rainfall relationship at a woodland-savanna transition zone in southern Africa. Issue 1 (2nd January 2022) - Hamilton, T; Archibald, S; Woodborne, S
Abstract : Southern Africa is dominated by fire-prone arid and semi-arid landscapes that are expected to experience increased maximum temperatures, rainfall variation and frequency of extreme rainfall events in the future. These conditions will affect fire and vegetation dynamics, but feedback and interactions among fire, rainfall and woody cover limit our ability to predict future ecosystem changes. Moreover, human activities can also drive changes in these components and their interactions. There are few long-term datasets available to monitor these changes over ecologically relevant time-scales. Here the combined analysis of a rainfall proxy, developed from a baobab tree core ( Adansonia digitata ) and fire proxy, from a sediment core, in the savanna-woodland transition zone in South Central Africa elucidates the history of two major drivers of savanna structure for the past 600 years. They show a system that oscillates between wooded and grassy vegetation states over time, as well as a change in the spatial scale of fires, which could be linked to human activities and recent fire management legislation.